The Magic Mirror And Other Stories - Enid Blyton
In Indonesian (Anak dalam Cermin) or in English version Dame Topple$1 (Bs Buns and other Stories by Enid Blyton.Serial Kumbang, thanks to my favourite story Dolly Pembuang Waktu, Kesalahan Teddy dan Karena Malas. These stories are great in teaching children I guess. Well at least , I still feel they did for me now.s